Study of vortex dynamics in a solar tower vortex generator - Singh J.; Kumar A.; Singh A.P.; Singh O.P. (My University, 2025)
Vortical flows, integral to fluid mechanics, significantly influence the performance and efficiency of various engineering applications. Utilizing a validated three-dimensional computational model, this study characterizes vortex structures and examines the impact of ambient conditions and the strategic positioning of vortex generators (swirler) at critical geometric locations, such as the throat, and regions above and below it, within a converging–diverging solar tower. The research explores the influence of swirler position on recirculation zone characteristics, focusing on center-to-center (C2C) distance, penetration length, and maximum width. When the swirler is positioned above or below the throat, C2C distance shows minimal change. However, placing the swirler exit at the throat significantly reduces C2C distance at the lowest velocity (0.13 m/s), due to a stable recirculation zone. This effect diminishes at higher velocities. Swirler position greatly affects penetration length, resulting in two distinct behaviors: Behavior A, dominated by swirler position, occurs when the swirler is above or below the throat, and Behavior B, which is velocity-dependent, is observed when the swirler exit is at the throat. The study also investigates the interaction between the recirculation zone and swirler exit flow, focusing on restriction and mixing ratios. The restriction ratio is higher below the throat (31 %) compared to the throat (27 %). The mixing ratio shows minimal variation with inlet velocity but significant variation with swirler position. Among the evaluated positions, placing the swirler below the throat results in the lowest swirl strength for most axial distances, except near the exit height, rendering it less suitable for water harvesting applications. These findings provide guidance for optimal swirler placement to achieve desired recirculation zone control and system performance. © 2024